STUDI LITERATUR: PENERAPAN METODE KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR PPKN - Salsabilla Azzahra; Arifin Maksum; Anggit Aruwiyantoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to see how effective the implementation of the Jigsaw cooperative method is to improve learning outcomes in the subject of Citizenship Education (PPKn) at the elementary school level. This study uses a literature study method by reviewing several journals and books from relevant previous studies. The results of the study indicate that the implementation of the jigsaw cooperative method in improving learning outcomes has a positive impact. Because, building students' self-confidence in expressing their opinions, learning motivation, cooperation and understanding of the students themselves regarding the subject of Citizenship Education (PPkn). This model forms individual responsibility in groups through the division of original groups and expert groups. Although effective, the success of this method depends on the role of the teacher in managing the class and seeing the characteristics of students while studying in class. Compared to other models such as Think-Pair-share and Group Investigation, the Jigsaw model is indeed superior in forming student involvement in class. Therefore, choosing the right model is very necessary in order to obtain maximum learning outcomes.